Intraarticular Involvement of Extraarticular Giant Cell Tumor of the Tendon Sheath in the Thumb of a Pediatric Patient: A Case Report - Aiko Makino; Susumu Saito; Tsuyoshi Taba (Journal of Plastic and Reconstructive Surgery, 2025)
Giant cell tumors of the tendon sheath (GCTTS) are locally invasive and have a high likelihood of recurrence in adults, but it is rare in children. Its potential to be invasive or recur has not been characterized. We present a 9-year-old patient with a dumbbell-shaped GCTTS that had small intraarticular and large extraarticular components with a narrow connection between them. This case suggests that GCTTS can be locally invasive in children. This case report could help hand surgeons who treat GCTTS in children.